Time-Series Analyses of the Impact of Sex Offender Registration and Notification Law Implementation and Subsequent Modifications on Rates of Sexual Offenses - Bouffard, Jeffrey A. (Crime & delinquency, 2019)
Sex offender registration and notification (SORN) laws were implemented to protect communities by increasing public awareness, and these laws have expanded over time to include registration by more types of offenders. Despite widespread implementation, research provides only inconsistent support for the impact of SORN laws on incidence of sexual offending. Using data from a large metropolitan area in Texas over the time period 1977 to 2012, and employing a number of time-series analyses, we examine the impact of the initial SORN implementation and two enhancements to the law. Results reveal no effect of SORN, or its subsequent modifications, on all sexual offenses or any of several specific offenses measures (e.g., crimes by repeat offenders). Implications for effective policy and future research are presented.